Morphometric Study of Cuora amboinensis in the Ex-Situ Conservation Area of Bengkulu University - Hardiansyah, Akbari; Karyadi, Bhakti; Parlindungan, Deni; Ruyani, Aceng; Sukarso, A.A. (BIOEDUKASI, 2024)
The Southeast Asian box turtle, Cuora amboinensis, known locally as the “Batok Turtle” is one of the world's most endangered turtle species. Conservation is needed to protect this species from the threat of extinction. Conservation efforts are complex and involve multiple scientific disciplines. This research was conducted in the Ex-situ Conservation area of ​​Bengkulu University, to determine the morphometric variations of adult C. amboinensis and determine the differences between males and females based on body size as a conservation effort. The research subjects were 20 adults (8 men and 12 women) of C. amboinensis. Several morphometric measurements that have been carried out include head width, carapace length, carapace width, curved carapace length, curved carapace width, carapace height, plastron length, plastron width, length of the midline on all plastron scales (sugar, humerus, pectoral, abdominal, femoral and anal), tail length, tail thickness, and body weight. Next, a t test was carried out to determine the morphometric characteristics of male and female C. amboinensis. The results of the analysis show that there are significant differences. C. amboinensis males have greater carapace length, tail length and tail thickness than females. C. amboinensis females have greater carapace height and humeral scale diameter than males.